High Level of HIV Drug Resistance and Virologic Nonsuppression Among Female Sex Workers in Ethiopia: A Nationwide Cross-Sectional Study. (15th April 2022) - Arimide, Dawit Assefa; Amogne, Minilik Demissie; Kebede, Yenew; Balcha, Taye T.; Adugna, Fekadu; Ramos, Artur; DeVos, Joshua; Zeh, Clement; Agardh, Anette; Chih-Wei Chang, Joy; Björkman, Per; Medstrand, Patrik
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To determine viral load (VL) nonsuppression (VLN) rates, HIV drug resistance (HIVDR) prevalence, and associated factors among female sex workers (FSWs) in Ethiopia. Methods: A cross-sectional biobehavioral survey was conducted among FSWs in 11 cities in Ethiopia in 2014. Whole blood was collected, and HIVDR genotyping was performed. Logistic regression analysis was performed to identify factors associated with VLN and HIVDR. Results: Among 4900 participants, 1172 (23.9%) were HIV-positive and 1154 (98.5%) had a VL result. Participants were categorized into antiretroviral therapy (ART) (n = 239) and ART-naive (n = 915) groups based on self-report. From the 521 specimens (ART, 59; ART-naive, 462) with VL ≥1000 copies/mL, genotyping was successful for 420 (80.6%) and 92 (21.9%) had drug resistance mutations (DRMs). Pretreatment drug resistance (PDR) was detected in 16.5% (63/381) of the ART-naive participants. Nucleoside reverse transcriptase inhibitor (NRTI), non-NRTIs (NNRTIs), and dual-class DRMs were detected in 40 (10.5%), 55 (14.4%), and 35 (9.2%) of the participants, respectively. Among 239 participants on ART, 59 (24.7%) had VLN. Genotyping was successfully performed for 39 (66.1%). DRMs were detected in 29 (74.4%). All 29 had NNRTI, 23 (79.3%) had NRTI or dual-class DRMs. VLN was associated with age 35 years or older, CD4 + T-cell count <350 cells/mm 3, and being forced into selling sex. PDR and acquired drug resistance were associated with CD4 + T-cell count <350 cells/mm 3 ( P < 0.001). Conclusions: The high VLN and HIVDR rates among FSWs underscore the need for targeted interventions to improve ART access and virologic monitoring to maximize the benefit of ART and limit the spread of HIV and HIVDR.